A PROSPECTIVE STUDY ON HYPONATREMIA IN CHILDREN WITH THE LOWER RESPIRATORY TRACT INFECTIONS ADMITTED IN PICU - SARISHMA, CHAPARALA; GESHMANJALI, KAKARALA; SAIKUMAR, BONELA; KORIPADU, SESHAGIRI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study has been undertaken to study hyponatremia in children with lower respiratory tract infections. The other objectives of the study were to evaluate the clinical and laboratory characteristics of children with hyponatremia and explore the relationship between hyponatremia and outcome about the duration of hospital stay and recovery/death. Methods: The study included children aged 2 months to 5 years who were referred to the PICU, GITAM Institute of Medical Sciences and Research, Visakhapatnam from October 2018 to September 2019 with the lower respiratory tract infections were included in the study. A thorough clinical examination and detailed history have been completed and recorded into a prestructured pro forma. Hematological investigations have been done in all cases. Chest X-ray has been done in all cases to delineate the radiological features of LRTI. A venous blood sample was collected and sent to the biochemistry lab to evaluate serum sodium and was estimated by the ion-selective electrode method analyzed by the radiometer. Results: 872 children were admitted to the pediatric intensive care unit during the study period. Among them, 100 children in the age group of 2 months to 5 years suffering from the lower respiratory tract infection were included in the study. Out of 100 cases of the lower respiratory tract infections, 59 cases were Pneumonia, and 41 cases were severe Pneumonia. Out of 100 cases, 68 cases accounting for 68% have normal sodium levels, 32 cases accounting to 32% had hyponatremia, and none had hypernatremia. Thus, third of the cases suffering from the lower respiratory tract infections had hyponatremia. The mean CRP in children with hyponatremia was 7.38 mg/dl, higher than children with normal sodium levels, that is, 2.30 mg/dl; this was also statistically significant (p<0.001). All 32 cases of hyponatremia and 68 cases of normonatremia recovered and were discharged. There was no mortality. Conclusion: Children with hyponatremia had a longer duration of hospital stay. Serum sodium levels are an important biomarker and should be measured in all children hospitalized for the lower respiratory tract infections.